The Effect of Camshaft Degreeing Towards Performance of a Passenger Car - Muhammad Haaziq bin Zulkefli; MD NORRIZAM BIN MOHMAD JA'AT @ MOHD NOH; SHAIFUL FADZIL BIN ZAINAL ABIDIN (Progress in Engineering Application and Technology, 2021)
The word "Degreeing Camshaft" means ensuring that the position of the camshaft in the engine coincides with that of the crankshaft, in order to synchronize their rotation. A procedure known as camshaft "degreeing" is employed to determine if a camshaft meets the manufacturer's specifications. This research was conducted with laboratory setup to analyze the performance of power and torque produced from each advance and retard exhaust timing of the passenger vehicle using Mustang Chassis Dynamometer. The test is conducted using 1.3L engine of Proton Saga FLX which has been changed to adjustable cam pulley for the exhaust. In addition, two types of test conducted which are full load test and part load test. For full load test, each of the exhaust cam pulley adjustment tested on wide open throttle using 4th gear on dynamometer. For part load test, each of the exhaust cam pulley adjustment tested on dynamometer to record the torque produced using 4th and 5th gear at 2000 rpm and 2500 rpm. Generally, advancing the exhaust cam pulley results the exhaust valve to opened and closed sooner while retarding the exhaust cam pulley will results the exhaust valve to opened and closed later. The result indicated that the later the exhaust valve open, the more torque and power gained at low RPM, while the sooner the exhaust valve open, the more high RPM power and torque gained. It is confirmed that the objectives of this study were achieved, the vehicle tested on the power curve test was identified and the amount of power and torque produced by the effect of exhaust cam pulley adjustment were studied.